Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Karyawan - Anas Nuruzzaman; Layla Chilyatul Baroroh; Rizki Mia Audina (CV. Syntax Corporation Indonesia, 2021)
Motivation and compensation as the main factors for assessing the work results (performance) of employees in the company. Because in addition to moral support, employees also have the desire to meet their needs through compensation obtained from the company. This research aims to obtain information on the